2012
DOI: 10.2341/10-375-c
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Clinical Evaluation of Composite Restorations in Posterior Teeth: Effect of Adhesive Systems

Abstract: This clinical study assessed the performance of posterior composite resins applied with the Adper™ Single Bond Plus (SB) and Adper™ Scotchbond SE (SE) adhesive systems and Filtek™ Supreme Plus composite resin, using modified US Public Health Service criteria. A total of 97 restorations were placed in posterior teeth by two calibrated operators. Application of the materials followed manufacturers' instructions. The restorations were evaluated by two examiners at baseline and after one year. Statistical analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…21 At the end of one year, composite resin restorations using either adhesive system showed equally satisfactory results. In another study, the performance of Filtek Supreme was found to be satisfactory even when used with a self-etch adhesive, Adper Prompt-L-Pop, over 15 months of clinical service.…”
Section: Discussionmentioning
confidence: 94%
“…21 At the end of one year, composite resin restorations using either adhesive system showed equally satisfactory results. In another study, the performance of Filtek Supreme was found to be satisfactory even when used with a self-etch adhesive, Adper Prompt-L-Pop, over 15 months of clinical service.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study, the clinical performance of Filtek Supreme used with either etch-and-rinse or self-etch adhesive in Class I cavities was evaluated. 21 At the end of one year, composite resin restorations using either adhesive system showed equally satisfactory results. In another study, the performance of Filtek Supreme was found to be satisfactory even when used with a self-etch adhesive, Adper Prompt-L-Pop, over 15 months of clinical service.…”
Section: Discussionmentioning
confidence: 92%
“…Due to the lower polymerization contraction of silorane composite when compared to the methacrylate composite, the interface is exposed in a significant way in a lower stress level, and silorane also presented lower adhesion to Strepococcus than conventional methacrylate ( Buergers et al, 2009 ). The evolution of adhesive systems should also be highlighted, aiming at smaller postoperative sensitivities and technical simplification, especially in the use of self-conditioning adhesives ( Sundfeld et al, 2016 , Baracco et al, 2016 ). However, more studies about this new and promising silorane polymeric system are necessary, as well as on different adhesive systems currently in use, in order to allow a good guidance to the surgeon dentist regarding the resinous material and more appropriate bond system for each case.…”
Section: Discussionmentioning
confidence: 99%